2008
DOI: 10.1586/14787210.6.6.805
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime: a reappraisal in an era of increasing antimicrobial resistance

Abstract: Cefepime is a 'fourth-generation' cephalosporin with an in vitro extended-spectrum of activity against Gram-negative and Gram-positive pathogens. Cefepime is approved for the treatment of moderate-to-severe infections, such as pneumonia, uncomplicated and complicated urinary tract infections, skin and soft-tissue infections, intra-abdominal infections and febrile neutropenia. In this article, we provide a critical review of pharmacodynamics, clinical management, pharmacokinetics, metabolism, pharmacodynamic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
77
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 151 publications
(153 reference statements)
1
77
0
3
Order By: Relevance
“…It is important to use existing antibiotics effectively whenever possible, using pharmacokinetics (PK) and pharmacodynamics (PD) analyses. Cefepime (CFP), a fourth-generation cephalosporin, is widely used to treat infections caused by GNB in both adult and pediatric patients (13,14). Several studies have shown the effectiveness and safety of CFP in treating urinary tract and lower respiratory infections in children (15,16).…”
mentioning
confidence: 99%
“…It is important to use existing antibiotics effectively whenever possible, using pharmacokinetics (PK) and pharmacodynamics (PD) analyses. Cefepime (CFP), a fourth-generation cephalosporin, is widely used to treat infections caused by GNB in both adult and pediatric patients (13,14). Several studies have shown the effectiveness and safety of CFP in treating urinary tract and lower respiratory infections in children (15,16).…”
mentioning
confidence: 99%
“…Keywords: cephalosporins, resistance, respiratory, infections in ambulatory care, but also parenterally, as an alternative to the amoxicillin -clavulanic acid or amoxicillin -sulbactam combinations [3,4]. It is often the case that the infectious agent is not isolated, hence no antibiogram is performed.…”
Section: Objectivesmentioning
confidence: 99%
“…In general, ESBLs are inhibited by the commercially available ␤-lactamase inhibitors but hydrolyze well the fourth-generation cephalosporin cefepime (FEP). On the other hand, AmpCs are not inhibited by inhibitors and do not hydrolyze FEP (1,(3)(4)(5). Therefore, FEP is suggested for the treatment of infections caused by AmpC producers (6)(7)(8).…”
mentioning
confidence: 99%